Resistance mechanisms of sugarcane cultivars to spittlebug Mahanarva fimbriolata - Dinardo-Miranda, Leila Luci; Fracasso, Juliano Vilela; Perecin, Dilermando [UNESP]; Oliveira, Mariana Cecilia de; Peixoto Lopes, Diego Olympio [UNESP]; Izeppi, Tiago Sabongi [UNESP]; Anjos, Ivan Antonio dos (Univ Sao Paolo, 2016)
The spittlebug Mahanarva fimbriolata (Stal) (Hemiptera: Cercopidae) is one of the most important pests of sugarcane in Brazil. Measures for population control are currently restricted to the use of chemical insecticides and fungus Metarhizium anisopliae, in part because very little information exists regarding resistance of sugarcane cultivars. Therefore, the aim of this study was to evaluate resistance mechanisms of 12 different sugarcane cultivars to M. fimbriolata to provide information for growers for pest management. Isolated buds of each cultivar were planted in pots and kept in a greenhouse for approximately three months. The pots were then moved to climate test chambers (26 +/- 1 degrees C; 70 +/- 10 % relative humidity; 12 h photoperiod) to carry out laboratory tests to evaluate adult feeding and female oviposition preferences (using both free-choice and no-choice tests) as well as the effects of cultivars on nymph development and cultivars tolerance to pest attack. The least attractive cultivars for adult feeding were IACSP96-2042 and IAC91-1099. Cultivars IACSP96-2042, IACSP96-3060 and IACSP94-2101 received the fewest eggs in the free-choice and no-choice oviposition tests and exhibited some level of antixenosis resistance. Cultivar IAC91-1099 showed the highest level of antibiosis resistance with a nymph survival rate in the roots of only 20 %. Finally, cultivar IACSP94-2094 appears to be tolerant to M. fimbriolata, as it did not show significant reductions in aboveground biomass weight, despite showing reduced leaf chlorophyll levels following pest attack.
Keywords: Saccharum spp.; antixenosis; antibiosis; tolerance